2003
DOI: 10.1021/ja035561f
|View full text |Cite
|
Sign up to set email alerts
|

A Sugar Discriminating Binuclear Copper(II) Complex

Abstract: We investigated the complex formation between various underivatized carbohydrates and the binuclear copper(II) complex 1, Cu(2)(bpdpo). A combined approach of UV/vis and CD spectroscopic investigations shows a large discrimination ability of 1 for structurally closely related monosaccharides in alkaline solution. The dominating form of the binuclear copper(II) complex consists of a [Cu(2)L(-)(H)(OH)(2)](+) species between pH 11 and 13, as determined from pH-dependent spectrophotometric titration experiments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 21 publications
4
100
0
Order By: Relevance
“…A main problem in the detection of neutral sugars with artificial receptors is competitive binding by bulk water. Elevated solution pH is therefore typically required to attain a useful degree of coordination and signal transduction in the most innovative new metal-based detection methods (4,5). There is an unmet demand for biomimetic sugar-sensing agents that function in neutral buffer solution (4,5).…”
Section: Resultsmentioning
confidence: 99%
“…A main problem in the detection of neutral sugars with artificial receptors is competitive binding by bulk water. Elevated solution pH is therefore typically required to attain a useful degree of coordination and signal transduction in the most innovative new metal-based detection methods (4,5). There is an unmet demand for biomimetic sugar-sensing agents that function in neutral buffer solution (4,5).…”
Section: Resultsmentioning
confidence: 99%
“…For related literature on paddle-wheel secondary building units, see : Chen et al (2006); Xue et al (2007); Striegler & Dittel (2003); Ma & Moulton (2007); Banerjee et al (2008); Saravanakumar et al (2004). For similar structures, see: Yakovenko et al (2009) ;Xue et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…Research interest in these compounds with copper(II) paddlewheel SBUs come from their structural diversity (Chen, et al, 2006;Xue et al, 2007) and potential applications in supramolecular medicinal chemistry (Ma & Moulton 2007), sugar discrimination (Striegler & Dittel 2003), molecular magnets (Banerjee et al, 2008;Saravanakumar et al, 2004;Yakovenko, et al, 2009), respectively. However, most…”
Section: S1 Commentmentioning
confidence: 99%
“…6,7,[11][12][13] For further development towards various analytes, the hosts based on Lewis acids other than boron may be promising but have scarcely been explored; only Co(II) and Cu(II) complexes were examined for sugar sensing. 14,15 We have successfully used the porphyrin complexes of zirconium(IV) for recognition and potentiometric detection of hard bases such as citrate and triphosphate. 16,17 Preliminary examinations indicated that the Zr(IV) porphyrin complexes react with polyphenols but not with polyols.…”
Section: Introductionmentioning
confidence: 99%